Implementation Of Village-Owned Enterprises (BUMDES) In Sibalung Village, Kemranjen District, Banyumas Regency - Ma'muri, Johar; Suryoto, Suryoto; Saputra, Anggara Setya; Lestari, Mery (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
ABSTRACT This research is entitled Implementation of Village Owned Enterprise Management (Bumdes) in Sibalung Village, Kemranjen District, Banyumas Regency. That the role of village economic development is very important in building community welfare. Rural development is one way to eradicate poverty. Village development can be improved through developing the potential of the village economy and becoming a forum for rural communities to develop themselves and their environment independently and in a participatory manner. Village communities have the same rights to participate in growing and developing in building an equitable order of life and welfare.  One of the new approaches that is expected to be able to become a driving force for development and the wheels of the village economy is through the establishment of village community economic institutions called Village-Owned Enterprises (BUMDes) as one of the mainstay programs in increasing village economic independence. This study uses a qualitative research method with a case study approach.  Where the location of this research is in Sibalung Village, Kemranjen District, Banyumas Regency, which is a village that has a BUMDes which is currently developing. The results of this study are based on the approach to implementing policies and organizational management. The aspect of policy implementation looks at the management of BUMDes in terms of policies, target groups, and environmental factors, of which the three aspects have been going quite well in the implementation of BUMDes in Sibalung Village.   Keywords: BUMDes, Policy Implementation ABSTRAK Penelitian ini berjudul Implementasi Pengelolaan Badan Usaha Milik Desa (Bumdes) Di Desa Sibalung Kecamatan Kemranjen Kabupaten Banyumas. Bahwa peran pembangunan ekonomi Desa menjadi sangat penting dalam membangun kesejahteraan masyarakat. Pembangunan pedesaan merupakan salah satu cara dalam upaya mengentaskan kemiskinan. Pembangunan desa dapat ditingkatkan melalui pengembangan potensi perekonomian desa dan menjadi wadah bersama masyarakat pedesaan dalam membangun diri dan lingkungannya secara mandiri dan partisipatif. Masyarakat desa memiliki hak yang sama untuk ikut tumbuh dan berkembang dalam membangun tatanan kehidupan dan kesejahtraan secara merata. Salah satu pendekatan baru yang diharapkan mampu menjadi penggerak pembangunan dan roda perekonomian desa adalah melalui pendirian kelembagaan ekonomi masyarakat desa yang disebut dengan istilah Badan Usaha Milik Desa (BUMDes) sebagai salah satu program andalan dalam meningkatkan kemandirian perekonomian desa. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Dimana lokasi penelitian ini dilakukan di Desa Sibalung Kecamatan Kemranjen Kabupaten Banyumas, yang mana merupakan desa yang memiliki BUMDes yang saat ini sedang berkembang. Hasil penelitian ini di dasarkan pada pendekatan implementasi kebijakan dan manajemen organisasinya. Adapaun aspek implementasi kebijakan melihat pengelolaan BUMDes dari sisi kebijakan, kelompok sasaran, dan faktor lingkungan, dimana dari tiga aspek tersebut sudah berjalan cukup baik pada pelaksanaan BUMDes di Desa Sibalung.   Kata Kunci: BUMDes, Implementasi Kebijakan